Legal Protection of Mental Hospital Patients Who Experienced Acts of Violence Committed by Medical Personnel (A Study at Dr. Arif Zainudin Regional Mental Hospital Surakarta, Indonesia) - Budiono, Arief; Wardani, Septyan Wijayanti Kusuma; Mamun, Abdullah al; Prasetyo, Yogi (Jurnal Penegakan Hukum dan Keadilan, 2023)
Every citizen, including mental hospital patients, has the right to legal protection, as they are vulnerable to experiencing acts of violence by medical personnel. This study aims to analyze the legal protection for people with mental health conditions who once experienced acts of violence committed by medical personnel. This study used sociological research methods with a descriptive qualitative research approach. This study used primary and secondary sources of data. The authors collected data through observation and interviews. The data in this research were analyzed and then described as narrative texts. The results showed that people with mental health conditions could obtain legal protection from acts of violence committed by medical personnel if they truly experienced bad treatment. It ensures that people with mental health conditions obtain their rights as citizens to be equally treated before the law. In undergoing their tasks, medical personnel must follow the SOP (Standard Operating Procedures), which includes prioritizing patient safety and comfort to keep patients from rebelling when their illnesses recur.